Comparison of Selected Methods of Stress Measurements in Ferromagnetic Materials - Żurek, Z.H. (Engineering Transactions, 2004)
Change in magnetisation of a ferromagnetic subjected to mechanical stress is known as Vilarie’s effect. The paper describes contactless measurement of stress based on this effect. The measurement signals generated by magnetoresistive transducer were compared to measurements of deformation conducted with strain gauge transducer at the same time. Qualitative and quantitative similarities have been observed in the recorded signals. The simplicity of the contactless stress and vibration measurement with magnetoresistive transducer has been demonstrated. This method makes possible measurements even if the material is characterised by Iow magnetostriction coefficient.